Advanced Electrical and Optical Microsystems for Biointerfacing. (14th July 2020) - Obaid, Sofian N.; Chen, Zhiyuan; Lu, Luyao
Abstract : Electrical and optical biointerfaces have contributed considerably to understanding biological systems. Recent advances in biocompatible materials, structure designs, and fabrication techniques have established flexible and minimally invasive electronic/optoelectronic platforms that laminate onto targeted surface regions or implant into precise locations of biosystems to monitor and control various biological processes at cell, tissue, and organ levels. Herein, recent progress in advanced biointegrated electrical and optical platforms is discussed. An overview of materials and device designs to form flexible and even stretchable electrodes is presented. Strategies to reduce tissue damage and foreign‐body response to improve chronic stability are described. State‐of‐the‐art wearable and implantable microsystems with/without wireless capabilities for bioelectrical sensing and stimulation, optical recording and modulation, and multimodal operation are highlighted. In conclusion, a discussion of the remaining obstacles for future research in these areas is provided. Abstract : Biointegrated and biocompatible electronic/optoelectronic devices are now widely adopted in biological and biomedical research as minimally invasive biointerfaces. Herein, recent progress in materials, structure designs, and fabrication techniques in electrical and optical biointerfaces is provided. State‐of‐the‐art wearable and implantable recording and/or stimulation technologies are summarized and the remaining challenges to be solved in the future are highlighted.